Autonomy and Job Satisfaction : The Moderating Effect of Perceived Supervisor Support A study on the Yemeni Context - Al-Marwani, Ahmed AbdulJalil Ahmed (2015)
Job autonomy has been recognized to be one of the main job characteristics in job design, leading to several favourable job outcomes such as job satisfaction. By definition, autonomy has been widely recognized to contain three main components. Yet, studies that address the three components individually are scarce. The purpose of this study was to investigate the relationship between each one of the three components of job autonomy and job satisfaction. This study also aims to examine the contextual influence of this relationship by testing the moderating effect of perceived supervisor support, and whether the latter relates directly to job satisfaction. The relationships are studied in the Yemeni organizational context, where only a handful of organizational behaviors studies have been conducted in the past. A sample of 153 Yemeni employees, from different organizations, completed self-administered questionnaires measuring job satisfaction, work autonomy and perceived supervisory support. The results showed positive, and moderate between two forms of autonomy, methods autonomy and schedule autonomy, and job satisfaction. However, there was no correlation between criteria autonomy and job satisfaction. Perceived supervisor support was positively related to job satisfaction, and it moderated the relationship between schedule autonomy and job satisfaction.